Kajian Studi Sistem Pemeliharaan Ternak Babi Yang Terdampak Asian Swine Fever (ASF) di Kota Palangka Raya - Noorrahman, Nabil Fariz; Imanuel, Robertho; Anjalani, Ria; Steffani, Ayulia (VITEK : Bidang Kedokteran Hewan, 2023)
This study aims to determine the effect of raising pigs in the city of Palangka Raya on the incidence of African Swine Fever (ASF). This research is field research using a survey method and the selection of pig pens was carried out using purposive sampling. Correspondents drawn from 15 pig farmers, and pig farming business actors were interviewed and observed about cases of ASF incidents on their farms. The research variables used were the pen system, expert system, health system, and handling system for pigs affected by ASF and not affected by ASF. Data analysis is presented in tabular form and described in the discussion. The research results showed that 14 farmers in the city of Palangka Raya were affected by ASF (93.33%). 11 correspondents (73.33%) had knowledge of ASF cases and immediately reported them to the relevant agencies and 10 correspondent (66.6%) reported them to the nearest veterinarian and 11 correspondent (73.3%) of breeders did not have cages quarantine separating pigs affected by ASF from those not affected by ASF. It was concluded that the rearing system for pigs in the city of Palangka Raya has an influence on the condition of pigs through prevention and a good rearing system.